REVIEWING NURISTANI LANGUAGES AND TRIBAL DIALECTS - AHMAD GUL MOMAND; LATIFULLAH GHAFOORI (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2023)
In eastern Afghanistan, Nuristan lays in mountains. Nursitan Province is located in eastern Afghanistan, on the Afghanistan - Pakistan border. Almost all valleys and rivers, home to indigenous people, rich of culture that date back to ancient civilization. As new modern world takes shape and almost all aspect of life has changed, very little changed in these valleys. Nuristan is home to eight major tribes and each tribe has its dialect. This paper illustrates Nuristani Languages and its dialects and tribes reside in valleys for thousand of years. Most Nuristanis are from the Kata Family and Janaderi Branch. However, there are other Nuristani tribes as well, some of the Kata of Janaderi people live in Ozhor (now Karimabad), Gobor, Buburat, Ayun, Broze and Mastuj. There is a very popular rock associated with this tribe located in Karimabad (Juwara) called kata bont (Kata is the name of the tribe; bont meaning